(3dSGf GdNhGUs - (3GdbRhjfj, GdCbG QVqj GdOjf, eMeO Hf GdMSf, J (B1096 (3g`s ((3YHO GdQShd GdNQSGfs)
(3ChdgG (B:s
(3GdMeO ddg (B..(3Gf gPg ChQGb eTMhfI HdWGFa GdahGFO ef GdYdhe GdMbI GdOjfjI hCWHGb eedhAI ef faGFS GdaQGFO ef GdeYGQa GdHQgGfjI GdjbjfjI LeYJ ajgG RHOI fJGFL GdbQGFM GdeGVjI ef UhGFH GdCfXGQ hVeeJ EdjgG (B...s
(3BNQgG (B:s
.. (3hMjfFP jYQVg GdUaGJ GdeYJHQI aj GdeTHg Hg hef LedJgG GdbOe JYQa GdTjA EPG CJi dg SJI CTgQ UGQ ehUhaG HGdbOe hgPG gh GdeWdhH aJOHQ hQGLY HYO GdJCed ajeG PcQfG (B.. (3gPG BNQ eG CQOfG Cf fNJe Hgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6/90s
(3GdPQjYI (B18/216s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GddZIs